The Flow Analysis and Performance of the Chicken Eggs Supply Chain in Konda District South Konawe Regency - Pujiastuti Kadang; Sitti Aida Adha Taridala; Munirwan Zani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
Chicken eggs are one of the livestock products that have sufficient demand. The supply chain of broiler eggs has a regulatory system related to product flow, information flow, and financial flow in the distribution process of broiler eggs. This study aims to analyze product flow, information flow, and financial flow in the supply chain of purebred chicken eggs in the Inti Ternak farm business and to analyze the performance of the purebred chicken egg supply chain in the Inti Ternak farm business. This research was carried out in Konda District, South Konawe Regency, from July 2021 to May 2022. The object of this research is the IntiTernak farm business using the case study method. In contrast, the determination of the sample on the traders uses the snowball sampling technique by following the product flow. The variables in this study are respondent identity, supply chain, and supply chain performance. Data analysis in this study used a quantitative descriptive method. Based on the study results, the supply chain of broiler eggs consists of 3 streams, namely product flow, information flow, and financial flow, and consists of leading actors and supporting actors. The product flow flows from the Inti Ternak farm business to the final consumer of broiler eggs. The flow of information flows in two directions from the Inti Ternak farm business to the final consumer. In contrast, the financial flow streams from the final consumer of broiler eggs to the Inti Ternak farm business. The performance of the broiler egg supply chain as measured by marketing margin analysis and farmer's share shows results that illustrate that marketing channel II is more efficient than marketing channel I.